Study on Durability of Concrete under Alkali-Aggregate Reaction. (9th June 2022) - Hei, Mingchang; Fayou, A.; Jia, Xiong; Peng, Wenbin; Yin, Chuan
Abstract : The alkali-aggregate reaction has always had a great impact on the safety and durability of concrete projects. Therefore, the study of concrete failure mechanism under alkali-aggregate reaction has become a hot topic in the engineering field. This paper takes the Longtanqing debris flow ditch concrete treatment project as the background. Based on the alkali-aggregate reaction inhibition test under different conditions, regression analysis and trend surface analysis were used to study the correlation between fly ash content, expansion rate of concrete specimens, and curing age. And the engineering measures are put forward to effectively inhibit the alkali-aggregate reaction: (1) the optimum amount of fly ash appears at 30%-40%, fly ash has the strongest ability to inhibit alkali-aggregate reaction; when the content of fly ash is less than 20%, the fly ash ability to inhibit alkali aggregate reaction is weak. (2) To lower the height of the alkali content of concrete, there is 35% of the grade I class F coal ash as concrete admixture.